1959
DOI: 10.1084/jem.110.6.887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the "Long Chain Reaction" as a Means for Detecting Type-Specific Antibody to Group a Streptococci in Human Sera

Abstract: Much evidence supports the concept that immunity to Group A streptococcal infection is type-specific; that is, that recovery from infection with one type of Group A streptococcus results in immunity to that type only. The M protein antigen in Group A streptococcal cell walls determines the serologic type specificity of various strains and is an important factor associated with strain virulence. Antibody to the M protein plays a fundamental role in immunity to Group A streptococcal infection and is, indeed, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1960
1960
1997
1997

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Most virulent strains exhibited the long chaining phenomenon. Suitable representatives of Types 1,3,4,5,6,12,14,19,30, and "Red Lake" were preserved by lyophilization in rabbit blood. Frozen stocks of some strains also were prepared by resuspending the cells sedimented from 40 ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most virulent strains exhibited the long chaining phenomenon. Suitable representatives of Types 1,3,4,5,6,12,14,19,30, and "Red Lake" were preserved by lyophilization in rabbit blood. Frozen stocks of some strains also were prepared by resuspending the cells sedimented from 40 ml.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that this phenomenon was dependent upon the interaction of M protein and its antibody. The long chain reaction was found useful for detecting human type specific antibody with almost the same sensitivity as the bactericidal test (12). Long chaining was also used recently by Wilson (13) to identify M protein in strains of streptococci.…”
mentioning
confidence: 99%
“…Long-Chain test. The test was performed according to a method previously described (25). Tests for Type-specific Antibody Responses by Enzyme-linked Immunosorbent Assays (ELISA ).…”
Section: Preparation Ofpep M Antigens For Injection For Skin Testingmentioning
confidence: 99%
“…Because virulent encapsulated streptococci grow in long chains in the presence of homologous type antiserum, and in very short chains in serum which does not contain type specific antibody, this index is a semiquantitative expression for the amount of anti-M antibody in the system. A threefold increase in mean chain length (index = 3), or greater, was considered a statistically significant test for type specific antibody (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…At critical levels, therefore, the bactericidal test could be positive and the long chain test negative. Occasionally, the reverse situation could occur due to nonspecific factors affecting phagocytosis (26,27). The degree of virulence of the test strain of streptococci also had an effect on the resulting indices when titers of serum antibody were low (Table I).…”
Section: Methodsmentioning
confidence: 99%